High-precision large-range optical fiber interferometric piezometer and its wideband interferometry for water pressure measurement - Wang, Shun (2022)
A high-precision large-range fiber-optic interferometric piezometer is designed, packaged, and demonstrated for pore water pressure measurement. The piezometer is an optical fiber extrinsic Fabry-Perot interferometer (EFPI), which comprises a fiber ferrule connector/flat contact (FC/FC) connector and an aluminum foil pasted on a thin metal plate. The EFPI forms a sealed chamber with only the outer plane of the aluminum alloy plate being subjected to the water pressure through another hydraulic chamber with a standard filter stone. The deformation of the metal plate is analyzed and simulated for parameter optimization by using the small deflection theory. By adopting the conventional wavelength tracking method, the theoretical simulation and experimental results show a high measurement accuracy of the cm level but a limited measurement range. To resolve the problem, several wideband interferometry (WBI) methods, including free spectral range (FSR)-based, spatial frequency, interference order, and fitted FSR, are employed to analyze the spectrum of the EFPI for comparison. The fitted FSR method has demonstrated its superiority in applications that require simultaneous high resolution and large measurement range. A gas pressure test verifies that the proposed piezometer can work in a wide range of up to 0.5 MPa that is equivalent to a water depth of 50 m. In addition, the proposed piezometer offers several advantages, such as cost-effectiveness, robustness, repeatability, and stability, which further benefits its practical application.